Macroeconomic Policies and the Balance of Payments in Pakistan : 1972-1986. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper describes developments in the balance of payments of Pakistan during 1972-86, focusing particularly on the factors that gave rise to external payments problems and the macroeconomics policies that were adopted by the authorities. While performance on the growth and inflation fronts compares favorably with other developing countries, the balance of payments remained persistently weak. A combination of favorable external shocks, such as the large increase in workers' remittances and sizable foreign aid inflows, allowed the economy some breathing room, but ultimately did not reduce the need for comprehensive fiscal and trade reforms to ensure medium-term viability of the balance of payments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet